A cell wall-targeting urease-derived peptide as a potential antifungal agent against Candida species - Ana Paula A. Perin; Julia C.V. Reuwsaat; Heryk Motta; Fernanda Cortez Lopes; Matheus V.C. Grahl; Andrea G. Tavanti; Marilene H. Vainstein; Charley C. Staats; Célia R. Carlini; Rodrigo Ligabue-Braun; Lívia Kmetzsch (Current Research in Microbial Sciences)
Candida species are the most common opportunistic fungi that cause cutaneous and systemic infections, mainly in immunocompromised patients. The emergence of antifungal resistance has underscored the urgent need for new antifungal drugs, as highlighted by the World Health Organization in 2022 with the release of its first-ever fungal priority list. In this context, antimicrobial peptides present promising candidates for the development of alternative antimicrobial agents. In this study, we evaluated the antifungal activity of the Proteus mirabilis urease β subunit (PmUreβ; 12.2 kDa) against Candida species. PmUreβ reduced the viability of the tested Candida species by over 50 % at concentrations ranging from 2.25 to 9 µM, with the extend of the effect varying according to species and incubation temperature. It also decreased Candida albicans biofilm formation by 30 % at a higher concentration (18 µM). The mechanism of action of PmUreβ involves disruption of the cell wall integrity, as C. albicans cells treated with the recombinant peptide were protected by sorbitol, exhibited increased deposition of chitin in the cell wall, formed cell agglomerates, and downregulated genes associated with cell wall biosynthesis. Additionally, PmUreβ did not appear to cause cell membrane damage, as evidenced by the absence of propidium iodide permeation in treated cells. This peptide also demonstrated a synergistic and predominantly additive effect with fluconazole against the emergent Candida auris. Importantly, no harmful effects were observed in mammalian cells. Our findings suggest that PmUreβ is a fungitoxic peptide with significant biotechnological potential for treating infections caused by antifungal-resistant pathogens.